Determination of optimum effective parameters on thermal buckling of hybrid composite plates with quasi-square cut-out using a genetic algorithm. Issue 1 (2nd January 2020) - Mahdavi, Sajad; Shaterzadeh, Alireza; Jafari, Mohammad
ABSTRACT: The thermal buckling load on perforated composite plates is affected by several parameters, including design variables such as cut-out orientation, fibre angle, bluntness of cut-out corners, cut-out size to plate size ratio and stacking sequence. This study investigates the effect of these parameters on the thermal buckling load of a composite plate with a quasi-square cut-out. Optimal values of the parameters are determined using a genetic algorithm to achieve the maximum buckling load. The composite used herein is a four-layer laminated composite plate. The stacking sequences of the plate are also studied. Stability equations are obtained using first order shear deformation theory. The results showed that a plate with a quasi-square cut-out is more resistant to thermal buckling than one with a circular cut-out; thermal buckling of a composite plate is dependent on various parameters, and the maximum thermal buckling load can be achieved by appropriate selection of these parameters.